An Information System Model for Online Driver's License for Department of Land Transport in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
The research aim to develop an information system model for online driver’s license for department of land transport in Thai supply chain and an evaluation of the model . Samples are ten experts in the field of information system and supply chain. Ten experts are selected by purposive sampling method. The obtained data are analysed using mean and standard deviation. The research result demonstrates the model consists of five elements namely main components, Supplier, Department of land transport, Finished person, Customers .The data analysed by using arithmetic mean and standard deviation an information system model for online driver’s license for department of land transport in Thai supply chain using Back-Box technique. The results from ten experts have evaluated the model and commented that the developed model showed high suitability which mean The model can develop information system,